Kneading curves for Lozi maps - Baptista, Diogo (2012)
We explore some analogy between unimodal tent maps of the interval and Lozi maps, defining the critical point and the kneading sequence of a Lozi map. Then, we show that the set of parameter plane curves corresponding to Lozi maps with some initial kneading sequence has a structure close to the tree of unimodal tent kneading sequences, introduced by Sousa Ramos.